2014
DOI: 10.1186/2045-824x-6-18
|View full text |Cite
|
Sign up to set email alerts
|

Lenvatinib, an angiogenesis inhibitor targeting VEGFR/FGFR, shows broad antitumor activity in human tumor xenograft models associated with microvessel density and pericyte coverage

Abstract: BackgroundLenvatinib is an oral inhibitor of multiple receptor tyrosine kinases (RTKs) targeting vascular endothelial growth factor receptor (VEGFR1-3), fibroblast growth factor receptor (FGFR1-4), platelet growth factor receptor α (PDGFR α), RET and KIT. Antiangiogenesis activity of lenvatinib in VEGF- and FGF-driven angiogenesis models in both in vitro and in vivo was determined. Roles of tumor vasculature (microvessel density (MVD) and pericyte coverage) as biomarkers for lenvatinib were also examined in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
312
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 414 publications
(326 citation statements)
references
References 41 publications
3
312
1
10
Order By: Relevance
“…It is an oral multikinase inhibitor of vascular endothelial growth factor (VEGF) receptor (VEGFR)1-3, fibroblast growth factor receptor (FGFR)1-4, platelet-derived growth factor receptor alpha (PDGFR-α), ret proto-oncogene (RET), and KIT proto-oncogene [3][4][5]. In the phase 3 trial, lenvatinib prolonged progression-free survival (PFS; hazard ratio for progression or death, 0.21; 99 %CI, 0.14-0.31, p<0.001) by 14.7 months (lenvatinib median PFS, 8.3 months) compared with placebo (median PFS, 3.6 months) [6].…”
Section: Discussionmentioning
confidence: 99%
“…It is an oral multikinase inhibitor of vascular endothelial growth factor (VEGF) receptor (VEGFR)1-3, fibroblast growth factor receptor (FGFR)1-4, platelet-derived growth factor receptor alpha (PDGFR-α), ret proto-oncogene (RET), and KIT proto-oncogene [3][4][5]. In the phase 3 trial, lenvatinib prolonged progression-free survival (PFS; hazard ratio for progression or death, 0.21; 99 %CI, 0.14-0.31, p<0.001) by 14.7 months (lenvatinib median PFS, 8.3 months) compared with placebo (median PFS, 3.6 months) [6].…”
Section: Discussionmentioning
confidence: 99%
“…A notable array of compounds have been described in recent years to (partially) inhibit FGFR, next to other Tyrosine Kinase Receptor (TKR), including Vascular Endothelial Growth Factor Receptor (VEGFR), Platelet Derived Growth Factor Receptor (PDGFR), Fms-like tyrosine kinase 3 (FLT-3), c-Kit (c-KIT), Rearranged during transfection (RET) and BCR-ABL. These compounds include Brivatinib (Cai et al, 2008), Lenvatinib (Yamamoto et al, 2014), Regorafenib (Wilhelm et al, 2011), Ponatinib (Gozgit et al, 2012), Dovitininb (Porta et al, 2015), Nintedanib (Dhillon, 2015), Pazopanib (Prince et al, 2009), Orantinib (Ohta et al, 2009), ENMD 2076 (Matulonis et al, 2013), Lucitanib (Bello et al, 2011), PBI 05204 (Hong et al, 2014), Sunitinib (Welti et al, 2011) and Cediranib (Wedge et al, 2005). Although some of them have achieved approval for use against several cancer types, this section only focuses on those multi-target inhibitors that have included a subset of patients with FGFR alterations (Table 1).…”
Section: Non-selective Fgfr Tkismentioning
confidence: 99%
“…Despite the in vitro studies, lenvatinib showed significant antitumor activity in five DTC xenograft nude mouse models (25). This supports the notion that lenvatinib specifically targets the microvascular environment dependent on angiogenic VEGFR and FGFR signaling pathways rather than tumor proliferation pathways or cell cycle.…”
Section: Preclinical Datamentioning
confidence: 53%